“Blood lead level among battery factory workers in low and middle-income countries: Systematic review and meta-analysis” - Olana, Ararso Tafese; Kumie, Abera; Abegaz, Teferi (Frontiers in Public Health, 2022)
Introduction: Lead is one of the most health-hazardous causes of acute and chronic poisoning at workplaces. It is one of the key public health issues which affects the health of working populations. Objective: This review aims to identify the pooled mean blood lead level among battery factories in low and middle-income countries Methods: The search methods were considered the following electronic bibliographic databases: google scholar, PubMed, and other grey literature. A funnel plot and Begg test were used to see the publication bias. The heterogeneity of studies was checked using I-square statistics with a cut of point 75% and the Joanna Briggs Institute (JBI) quality assessment tool was applied to ensure the quality of the included articles. A random-effect model was applied to pool the blood lead level intoxication. The sub-group analysis was conducted by country and year of publication to control heterogeneity and to show variation. The search strategies were developed using different Boolean operators. Through the search strategies, 135 articles were identified. Of the total of identified articles, 43 full-text articles were selected for evaluation, and finally, eighteen (18) articles fit the inclusion criteria. Results: A total of 18 studies were included in the meta-analysis and the mean pooled blood lead level among lead battery factory workers in low and middle-income countries was 38µg/dl (95% CI: 30.68-45.3). In subgroup analysis by year in the random effect model, the pooled mean of blood lead level from 2006- 2011= 43.20 µg/dL (35.91-50.50), 2012-2015 = 37.78µg/dl (25.228-50.29) and 2016-2020 = 36.53µg/dl (19.44-53.62). Conclusions: This review showed that the pooled mean blood lead level of workers exposed to lead battery factories was (38µg/dl) which is above the threshold limit value (20µg/dl). Therefore, attention should be given by employers, government, and researchers to improve the health of working populations exposed to lead exposure in low and middle-income countries through the provision of occupational health and safety services in the sector.